Politics, Religion and Hate Speech in Zimbabwe. - Machingura, Francis (Langaa RPCIG, 2023)
This book is empirically grounded on Zimbabwe and looks at hate speech as a bad omen for any society, family, nation and organisation. Hate speech divides and kills any peace, unity, tolerance, inclusivity, philosophy, race and geographical area, sacred places of worship, freedoms, identities, culture, unity and development in any space. It is not a good recipe for both animate and inanimate. It is never a solution to be applied in any geographical location. Hate speech, conflict and violence usually go together. The book clearly shows that, hate speech must never be tolerated in any religion, space (both private and public spaces), scriptures, society and nation. It is poisonous and manifests in different forms such as language (verbal or electronic), discriminations, beliefs, practices, laws, censorship, graffiti and even physical assault.
Hate Speech and the Bible
Keywords: Hate speech -- Zimbabwe.; Zimbabwe -- Religion.; Propagande haineuse -- Zimbabwe.; POLITICAL SCIENCE / World / African.; Politics and government.; Africa.